Implementation of the Student Teams Achievement Division (STAD) Cooperative Learning Model in Improving Students' Learning Motivation in Intensive Class I Fiqh Learning A TMI Putra Al-Amien Prenduan Sumenep Madura. - Riski Yanto; Musleh Wahid (Penerbit Hellow Pustaka, 2025)
The STAD type cooperative learning model is one of the simplest learning methods that emphasizes student activity and interaction to motivate each other and understand the subject. In the learning approach, the teacher of class one intensive A still relies on the conventional approach, namely lectures. Teachers may not realize that students feel less enthusiastic because there is no change in the situation in the classroom. The causal factor is the lack of motivation of students in class one intensive A in learning in the classroom which is triggered by the learning model applied by the teacher of fiqh in class one intensive A, resulting in active teachers and passive students. Qualitative research is a non-statistical and intersubjective research in understanding phenomena (events, conditions) in depth about the subject being studied in a natural context. The research approach reveals a problem or event that exists now. The results of the study emphasize an objective description of the actual state of the object being studied. In this study, the researcher attempted to identify efforts to improve student learning motivation through observation, interviews and documentation of fiqh learning in class one intensive A at MTs TMI Prenduan. The results of this study are. 1). STAD type cooperative learning can increase students' learning motivation such as (a) they have great hopes and ideals; b) interesting learning and c) a conducive learning environment so that students can learn well and comfortably. 2.) Three factors that cause the learning process to be hampered such as: taking a lot of time in preparing learning, the number of students is too many so that teachers are less than optimal in observing learning activities and require special skills for teachers.